DIAGNOSTIC CRITERIA FOR BULIMIA NERVOSA: FREQUENCY AND DURATION OF EPISODES - Martins, Manuela Simões Pires; Toledo, Rodolfo Ricardo; Costa, Jamilly de Fátima Moraes; Moraes, Rodrigo Machado Costa; da Cruz, Wellington Nascimento (Seven Editora, 2026)
This study consists of a narrative literature review aimed at synthesizing contemporary scientific evidence on the diagnostic criteria for Bulimia Nervosa (BN), focusing on the frequency and duration of episodes. BN is a serious eating disorder characterized by recurrent episodes of binge eating followed by inappropriate compensatory behaviors to avoid weight gain, such as self-induced vomiting, laxative use, or fasting. According to the DSM-5 criteria, diagnosis requires that both binge eating and compensatory behaviors occur, on average, at least once a week for a minimum period of three months. This change in the frequency threshold, reduced compared to DSM-IV, was fundamental in increasing clinical sensitivity and allowing for earlier intervention. The severity of the disorder is classified weekly based on the frequency of inappropriate compensatory behaviors, ranging from Mild (1 to 3 episodes) to Extreme (14 or more episodes). The high frequency of purging episodes is directly correlated with the severity of medical complications, such as electrolyte imbalances. It is concluded that an accurate diagnosis depends on the rigorous application of the DSM-5 time and frequency criteria, careful distinction from other disorders (such as Binge Eating Disorder), and a multidisciplinary assessment that includes psychiatric comorbidities and the identification of body image distortion.